OPTIMIZING OF NURING MANAGEMENT ROUNDS AND IMPLEMENTATION OF DISCHARGE PLANNING IN FATMAWATI HOSPITAL JAKARTA: DOI: https://doi.org/10.35654/ijnhs.v2i1.80 - Sancka Stella (International Journal of Nursing and Health Services (IJNHS), 2019)
Abstract The results of the study identified the existence of obstacles in the implementation of discharge planning which had an impact on the lack of optimization of discharge planning implementation and the determination of the length of stay of the patient. The author uses the case study method. The innovation agreed upon with the nursing manager was in the form of implementing a nursing management round which was expected to have an impact on improving the implementation of discharge planning, as well as revisions to the standard operating procedures and the discharge planning documentation in accordance with Standard Nasional Akreditasi 2018. The result is an increase in knowledge of the head nurse and clinical care manager related to nursing management rounds (49.25%) and experience improvement (39.13%). Standard operational procedure of discharge planning draft and discharge planning form are agreed upon by the nursing manager. Resocializing discharge planning to doctors, nurses, nutritionists, pharmacists, and other health workers is needed to support patient safety and patient comfort before returning home.